Case report: Single-session double-Ilizarov lengthening technique in the treatment of a child with congenital fibular deficiency - Shu, Wen; Yue, Changjie; Zhong, Haobo; Tang, Xin (Frontiers in Pediatrics, 2022)
Background: Congenital fibular deficiency is a rare disease with a broad spectrum of deformities. Associated anomalies complicate the symptoms of patients and, consequently, individualized treatments that aim at normal function and acceptable appearance. Case presentation: We present a case of congenital femoral and fibular shortening in the right lower limb with foot anomaly at school age. The patient underwent limb lengthening of single session on right femur and tibia at the same time using a double-Ilizarov frame. The functional and cosmetic of his right lower extremity achieved a good outcome. Complications were minimised other than superficial infection. Treatment lasted for 9.2 months, allowing for returning the patient to functional activity as soon as possible. Conclusion: The satisfactory result can be obtained with limb lengthening of single session using double Ilizarov external fixators for the treatment of congenital fibular deficiency at school age.